The osteological series from Cabeço Da Amoreira (Muge, Portuga) - Eugénia Cunha; Francisca Cardoso (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In the present paper we present the first anthropological results for one of the most classic European Mesolithic sites, the Cabeço da Amoreira, hereafter Amoreira, on the Muge tributary of the Tagus River in central Portugal. Apart from this one, there are three more shell middens on the Tagus river: Moita do Sebastião, Cabeço da Arruda and the lesser known, Cova da Onça. While human remains from Moita and Arruda are well known, the osteological material from Amoreira was never analised. Thus the anthropological data presented here —a set of 21 individuals this far unpublished— make an important contribution to our understanding of the Mesolithic people who inhabited the Iberia Peninsula.